Evaluation of diazepam as a drug treatment for water hemlock (Cicuta species) poisoning in Spanish goats. (15th January 2022) - Green, Benedict T.; Stonecipher, Clinton A.; Welch, Kevin D.; Lee, Stephen T.; Cook, Daniel
Abstract: Water hemlocks ( Cicuta spp.) are toxic members of the Apiaceae plant family. The best drug treatment for the convulsions associated with acute water hemlock poisoning in livestock and humans has not been determined experimentally. This work compared the therapeutic actions of benzodiazepines (diazepam) and barbiturates (phenobarbital) on water hemlock poisoning in a goat model. C. maculata tubers were orally dosed to goats. Experimental groups consisted of; control saline; 20 mg/kg phenobarbital; 1.0 mg/kg diazepam; 10 mg/kg diazepam; and 1.0 mg/kg diazepam administered as needed to moderate convulsions by intravenous (i.v.) infusion. Diazepam provided nearly instant control of convulsions. Clinical signs of poisoning were completely controlled for the duration of the experiment in the goats that received the 10 mg/kg diazepam dose. These results suggest that diazepam is effective at managing the clinical signs of water hemlock poisoning in goats. We speculate that diazepam can be used as a potential treatment for water hemlock poisoning in other livestock species and humans. Graphical abstract: Image 1 Highlights: This work compared the actions of benzodiazepines and barbiturates on water hemlock ( Cicuta maculata ) poisoning in goats. The benzodiazepine, diazepam, was effective at managing the clinical signs of water hemlock poisoning. Diazepam is a potential treatment for water hemlock poisoning in other livestock species and humans.